N‐butylscopolammonium bromide causes fewer side effects than atropine when assessing bronchoconstriction reversibility in horses with heaves. (25th February 2014) - de Lagarde, M.; Rodrigues, N.; Chevigny, M.; Beauchamp, G.; Albrecht, B.; Lavoie, J. P.
Summary Reasons for performing study Bronchospasm results in airway obstruction in horses with heaves. Atropine is the most potent bronchodilator drug currently available for horses, but is associated with side effects that limit its use. Like atropine, N‐butylscopolammonium bromide (NBB) is an anticholinergic agent with bronchodilatory properties. Objectives To compare the bronchodilating effects and side effects of atropine and NBB in horses with heaves. Study design Cross‐over experiment using horses with heaves. Methods Eight horses with heaves were administered atropine and NBB, using a cross‐over design. Heart rate, pupillary dilatation, transrectal palpation, lung mechanics (maximal changes in transpulmonary pressure, pulmonary resistance and elastance) and arterial blood gases were assessed before and 10 and 30 min after drug administration. Results One horse treated with atropine developed colic. Significant pupillary dilatation was observed only with atropine. Tachycardia developed in all horses, but was more marked with atropine. Lung function improved with both drugs, but elastance values had returned to baseline at 30 min with NBB. There was no improvement in arterial hypoxaemia with either drug. Conclusions The study indicated that the bronchodilatory properties of NBB were not statistically different from those of atropine, but were of shorter duration. N‐butylscopolammonium bromide was associated with fewer systemic side effects, and therefore NBB should be preferred over atropine when assessing the reversibility of airway obstruction in horses.